Complete Ipsilateral Femoral Approach Using an Iliac Branch Device to Preserve a Sole Internal Iliac Artery After Aortic Stent-Graft Placement. (October 2016) - Rieß, Henrik Christian; Kölbel, Tilo; Diener, Holger; Heidemann, Franziska; Debus, E. Sebastian; Rohlffs, Fiona; Tsilimparis, Nikolaos
Purpose: To report implantation of an iliac branch device (IBD) for preserving antegrade blood flow to a sole internal iliac artery (IIA) via an ipsilateral approach during endovascular repair to reline an aortobi-iliac allograft.Technique: The technique is described in a 55-year-old man with an enteric fistula involving an aortobi-iliac Y-prosthesis. After complete excision, the prosthesis was replaced by an allograft. Due to rebleeding and resuturing of the graft, total stent-graft relining of the allograft was planned with preservation of the sole left IIA using an iliac side branch (ZBIS). During introduction of a 12-F sheath over the allograft's neobifurcation to establish a femorofemoral through-and-through approach, the allograft ruptured. A compliant balloon was inflated to control the hemorrhage. The IBD was first fully deployed, followed by stent-graft relining. Consequently, stent-graft implantation in the left IIA using a crossover maneuver was no longer feasible, so a 0.035-inch super stiff wire was introduced through the IBD's 20-F sheath. A 12-mm semi-compliant balloon was inflated in the common iliac artery above the iliac branch to act as an abutment for a 7-F sheath to run over the stiff wire into the IIA for delivery/deployment of a stent-graft.Conclusion: It is feasible to use a complete ipsilateral femoral approach for IBD implantation after aortic stent-graft placement.